Analysis of RGTK Utilization in Optimizing Elementary School Teacher Performance in West Pontianak - Ari Kusdiyanto; Martono; Dede Suratman; Kurnia Ningsih; Eva Faja Ripanti (Universitas Muhammadiyah Sumatera Utara, 2026)
This study aims to analyze the utilization of the Independent Training feature in the Teachers and Education Personnel Space (RGTK) in optimizing the performance of elementary school teachers in West Pontianak. The study used a qualitative approach with a descriptive design. Data were collected through participant observation, semi-structured interviews, and documentation with teachers, principals, and officials from the Education Office. Data analysis was conducted using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawing. The results show that the utilization of RGTK is still suboptimal and tends to be administrative, with external motivations dominating the platform's use. Inhibiting factors include time constraints, low intrinsic motivation, and a lack of mentoring and institutional support. The role of principals and the Education Office has not fully supported the optimization of RGTK's sustainable use. Nevertheless, RGTK has the potential to improve teacher performance, especially in the aspect of lesson planning, but its implementation remains inconsistent. This study confirms that optimizing digital platforms for teacher professional development requires systemic support, reflective leadership, and strengthening a culture of independent learning.